2006
DOI: 10.1021/bi0611917
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of Nucleotide Association and Kinetic Characterization of Myo1b

Abstract: Myo1b is a widely expressed myosin-I isoform that concentrates on endosomal and ruffling membranes and is thought to play roles in membrane trafficking and dynamics. It is one of the best characterized myosin-I isoforms and appears to have unique biochemical properties tuned for tension sensing or tension maintenance. We determined the key biochemical rate constants that define the actomyo1b ATPase cycle at 37 °C and measured the temperature dependence of ATP binding, ADP release, and the transition from a nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
32
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 40 publications
7
32
0
Order By: Relevance
“…The ratio of affinities (K 10 ∕K 6 ¼ K DA ∕K A ) has been termed the coupling constant (22,23), and the calculated value of 5.5 is similar to previously published values for myo1b (28,29); however, it is larger than a previously reported value for myo1c (10). Based on the solution kinetics, ADP release is expected to be rate limiting for actomyosin detachment at saturating ATP concentrations; however, a slower transition (likely associated with phosphate release) (16,19) limits the rate of the overall ATPase cycle. The effective duty ratio of myo1c 3IQ at 100 μM actin and saturating ATP concentrations is 0.11.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…The ratio of affinities (K 10 ∕K 6 ¼ K DA ∕K A ) has been termed the coupling constant (22,23), and the calculated value of 5.5 is similar to previously published values for myo1b (28,29); however, it is larger than a previously reported value for myo1c (10). Based on the solution kinetics, ADP release is expected to be rate limiting for actomyosin detachment at saturating ATP concentrations; however, a slower transition (likely associated with phosphate release) (16,19) limits the rate of the overall ATPase cycle. The effective duty ratio of myo1c 3IQ at 100 μM actin and saturating ATP concentrations is 0.11.…”
Section: Resultssupporting
confidence: 79%
“…The rate constants that define the myo1c actin-activated ATPase pathway in solution are very similar to myo1b (10,12,16,19), a closely related myosin-I isoform that has actin-detachment kinetics that are exquisitely sensitive to tension (20). Myo1b is suited to function as a tension-sensitive anchor, transforming from a low duty-ratio motor to a high duty ratio-motor with forces resisting its working stroke >0.5 pN.…”
mentioning
confidence: 99%
“…Myosin 1b has been shown to have an unusually marked temperature dependence (29). We made preliminary studies of the temperature dependence of some of the key steps in Myo1c 1IQ and found that Myo1c shares some of the temperature dependence of Myo1b but is also quite distinct (see SI Text and Fig.…”
Section: Methodsmentioning
confidence: 88%
“…4) (7,13). Experiments were performed in the presence of 50 μM ATP to ensure that the rate of ATP binding did not limit the rate of detachment (7,17). Long attachment durations at higher forces are apparent in the time traces of all four myo1b proteins, but it is clear that the shorter isoforms have shorter attachment durations (Fig.…”
Section: Resultsmentioning
confidence: 99%